2022
DOI: 10.3389/fpsyg.2022.1003231
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the self-reported physical fitness and self-rated health, mental health disorders, and body satisfaction among Chinese adolescents: A cross-sectional study

Abstract: Background: Physical activity (PA) and Physical fitness (PF) have received tremendous attention in the field of physical and mental health. However, limited attention has been given to the associations of self-reported physical fitness with some health-related outcomes. Given the COVID-19 pandemic is still active in many Chinese regions, assessing health-related physical fitness (HRPF) in adolescents using field-based assessment (such as a shuttle run for cardiorespiratory fitness) is unrealistic, therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…PA is an important predictor of self-perceived health in adolescents (24). Thus, results from a review study showed that most of the included cross-sectional studies reveal that high PA is associated with better SRH in adolescents (8,25). Furthermore, only four studies did not report a significant association between physical activity and SRH in children and adolescents, which can be explained by the limitations of the studies' designs (8).…”
Section: Introductionmentioning
confidence: 99%
“…PA is an important predictor of self-perceived health in adolescents (24). Thus, results from a review study showed that most of the included cross-sectional studies reveal that high PA is associated with better SRH in adolescents (8,25). Furthermore, only four studies did not report a significant association between physical activity and SRH in children and adolescents, which can be explained by the limitations of the studies' designs (8).…”
Section: Introductionmentioning
confidence: 99%
“…Self-rated health (SRH) is a widely used measure in public health to assess an individual’s overall health ( Liu et al, 2023 ; Jylhä, 2009 ; Shi et al, 2022 ). It refers to the perception of one’s health status ( Kastelic et al, 2021 ) and serves as an important indicator of an individual’s general well-being, reflecting not only their physical health but also their mental, emotional, and social health ( Nieminen et al, 2010 ; Vie et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To verify the effects of healthy movement behaviours on health outcomes, it is necessary to further assess the association between meeting the 24-hour movement guidelines and SRH in other countries, such as China. It has been documented that PA, ST and sleep duration are independent factors of SRH in Chinese adolescents ( Chen et al, 2022b ; Shi et al, 2022 ). However, little is known about their integrative association ( i.e., in combination with PA, ST and sleep duration) with SRH.…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction is an overall and cognitive appraisal of individuals' life ( 6 , 7 ). Life satisfaction is a crucial component of positive psychology, which can be defined as a subjective sensitivity of the multiple life aspects in people ( 8 10 ). Life satisfaction involves a cognitive assessment in humans' whole character of life ( 11 ), which also includes self-satisfaction, family satisfaction, as well as school satisfaction ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the empirical evidence, physical activity (PA) has been regarded as an optative strategy to boost children's and adolescents' mental ( 25 ) and physical health ( 26 , 27 ). Recently, there is evidence showing that higher PA levels are related to children's and adolescents' life satisfaction ( 10 , 28 ). In general, PA and life satisfaction's positive relationship has been reported in several previous studies ( 29 32 ).…”
Section: Introductionmentioning
confidence: 99%